Persepsi Followers Instagram Pada Bening's Clinic Solo Dalam Membangun Brand Image Instagram Followers' Perception of Bening's Clinic Solo in Building Brand Image - Ramadhana, Vilawati; Suryo, Herning; Kusumo Aji, Haryo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This research aims to analyze Instagram followers' perceptions of Bening's Clinic Solo in building a brand image. This research uses a qualitative approach with a document study method. Data collection was carried out through in-depth interviews with active followers on the Bening's Clinic Solo Instagram account. Data analysis uses a perception process model, including selection (sensation and attention), interpretation (organization and categorization), and rounding (judgment and conclusions). The research results show that followers' perceptions of Bening's Clinic Solo are influenced by various factors, such as content visualization, interactions with the clinic, and testimonials from other users. The positive perception formed can contribute to the formation of a strong brand image and attract the interest of potential new consumers. Keywords: Perception, Instagram Followers, Bening's Clinic Solo, Brand Image